Sex differences in macronutrient intake and adherence to dietary recommendations: findings from the UK Biobank - Bennett, E; Peters, S; Woodward, M (BMJ Publishing Grou, 2018)
Objectives: To characterise sex differences in macronutrient intakes and adherence to dietary recommendations in the UK Biobank population. Design: Cross-sectional population-based study. Setting: UK Biobank Resource. Participants: 210 106 (52.5% women) individuals with data on dietary behaviour. Main outcome measures: Women-to-men mean differences in nutrient intake in grams and as a percentage of energy and women-to-men ORs in non-adherence, adjusting for age, socioeconomic status and ethnicity. Results: There were sex differences in energy intake and distribution. Men had greater intakes of energy and were less likely to have energy intakes above the estimated average requirement compared with women. Small, but significant, sex differences were found in the intakes of all macronutrients. For all macronutrients, men had greater absolute intakes while women had greater intakes as a percentage of energy. Women were more likely to have intakes that exceeded recommendations for total fat, saturated fat and total sugar. Men were less likely to achieve the minimum recommended intakes for protein, polyunsaturated fat and total carbohydrate. Over 95% of men and women were non-adherent to fibre recommendations. Sex differences in dietary intakes were moderated by age and to some extent by socioeconomic status. Conclusions: There are significant sex differences in adherence to dietary recommendations, particularly for sugar. However, given the increased focus on food groups and dietary patterns for nutritional policy, these differences alone may not be sufficient for policy and health promotion. Future studies that are able to explore the sex differences in intakes of different food groups that are risk factors for diet-related diseases are warranted to improve the current understanding of the differential impact of diet on health in women and men.